Pemberdayaan Siswa SMK Kuningan Melalui Pelatihan Junior Web Developer Dalam Pengembangan Web - Raditya Danar Dana; Rudi Kurniawan; Adbdul Muhyi; Ade Awaludin (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Junior Web Developer Training is an empowerment program for SMK students in Kuningan that aims to improve their skills in web development. The program is designed to equip students with knowledge and skills relevant to the digital industry, including HTML, CSS, JavaScript, and the use of modern frameworks. Through a project-based approach, the training enables participants to develop web applications that meet the needs of the industry and the local community. The training delivery method includes a balance of theory and practice, with mentoring sessions from professional practitioners. Evaluation is based on individual assignments and group projects to ensure understanding and application of the material. In addition, participants were also given insights into industry trends as well as soft skills such as communication and teamwork that are essential in the world of work. The results of the training showed a significant improvement in participants' technical skills, as seen in their ability to build functional web projects. In addition, the program also contributed to the students' increased confidence in facing the challenges of the world of work in the field of technology. The success of this training opens up opportunities for broader development of similar programs, with the hope that it can become a model of empowerment for SMK students in other areas.With this training, it is hoped that students will not only have good technical competence, but also readiness to enter the technology industry. Improved skills in web development can be a valuable asset for them to pursue a career as a professional developer or even create their own job opportunities through digital entrepreneurship.